Effects of pressure levels in three-cascade storage system on the overall energy consumption in the hydrogen refueling station. (3rd September 2021) - Xiao, Lei; Chen, Jianye; Wu, Yimei; Zhang, Wei; Ye, Jianjun; Shao, Shuangquan; Xie, Junlong
Abstract: Studies show that compared with the one-buffer system, the cascade storage system has lower energy consumption in high-pressure hydrogen refueling stations. In the present study, practical dynamic models of the whole hydrogen refueling process are established to evaluate the energy consumption. Accordingly, the filling performance of the three-cascade storage system and single tank storage system are analyzed. Moreover, the impact of the three pressure levels and the charging sequence of the three tanks on the energy consumption are investigated. The obtained results show that changing from one buffer to three tanks gives a total energy saving of approximate 34%. For the three-cascade storage system, the total energy consumption increases approximately linearly with the increase of the pressure of the high-pressure tank. Whereas it shows concave curve shape trends with the increase of low-pressure level and the medium-pressure level. Furthermore, the charging sequence from the low-pressure buffer to the high one decreases the total operation energy consumption to a value slightly lower than the adverse charge sequence. Graphical abstract: Image 1 Highlights: Validated thermodynamic model is established for refueling process. Compared to one buffer, energy consumption in three-cascade reduces by 34%. Proper combination of three pressure levels reduces energy consumption. Buffer charging sequence from low to high slightly reduces energy consumption.